2014
DOI: 10.1515/cclm-2014-0011
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive protein and migraine. Facts or speculations?

Abstract: Migraine is a highly prevalent and frequently disabling disorder. Since the pathogenesis of this condition has a strong inflammatory component and migraine is significantly associated with cardiovascular disease, we assess whether C-reactive protein (CRP) may be epidemiologically or casually linked with migraine. An electronic search on Medline, Scopus and Web of Science produced 17 studies reporting original data about the epidemiological association between CRP and migraine (1 retrospective, 1 interventional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
3
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 36 publications
2
40
3
1
Order By: Relevance
“…There are emerging evidences that several cytokines such as IL-6, TNF, IL-10 are implicated in the pathogenesis of migraine attacks, wherein these inflammatory cytokines can promote sensitization of nerve endings during recurrent migraine attacks (27,28). Moreover, serum levels of CRP have been demonstrated to be linked with migraine (6). In support of this, our study observed an increased serum concentration of CRP in migraine patients compared with healthy controls.…”
Section: Discussionsupporting
confidence: 85%
“…There are emerging evidences that several cytokines such as IL-6, TNF, IL-10 are implicated in the pathogenesis of migraine attacks, wherein these inflammatory cytokines can promote sensitization of nerve endings during recurrent migraine attacks (27,28). Moreover, serum levels of CRP have been demonstrated to be linked with migraine (6). In support of this, our study observed an increased serum concentration of CRP in migraine patients compared with healthy controls.…”
Section: Discussionsupporting
confidence: 85%
“…On the other hand, monocyte and MHR values were significantly higher in MwA patients. In the literature, some inflammatory biomarkers such as high leptin, Soluble urokinase plasminogen activator receptor, apolipoprotein E, and CRP levels were found to be increased in MwA patients supporting the inflammatory hypothesis [24][25][26][27]. Further studies with serum markers and inflammatory citokines are needed to evaluate the possible relationship.…”
Section: Discussionmentioning
confidence: 94%
“…Emerging evidences about the migraine pathogenesis showed that several cytokines mainly IL-6, TNF, and IL-10 are involved, wherein sensitization of nerve endings can be promoted by these inflammatory cytokines during recurrent migraine attacks [15,16]. Moreover, increased CRP values have been demonstrated to be related to migraine, and have been considered to be an inflammatory marker in migraine patients [17]. Consistent with these studies, our study revealed an increased serum concentration of ESR and hsCRP levels in patients with migraine compared with healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
“…It is through this mechanism that the resultant inflammation, oxidative stress, endothelial dysfunction, and hypercoagulability may lead to pathological vascular changes [15]. Also, there are some studies indicating that inflammation has a significant influence on the pathophysiology of atherosclerosis [12,13,16] [17][18][19][20][21][22]. Although there is great heterogeneity in the findings of these studies, Lippi et al emphasized that there could be a potential epidemiological association between migraines and increased CRP concentrations, and that it may be possible to relieve migraine symptoms and to reduce the risk for cardiovascular disease by decreasing the CRP levels, indicating a need for further studies on this topic [17,23].…”
Section: Discussionmentioning
confidence: 99%